Gut Microbiota Species Can Provoke both Inflammatory and Tolerogenic Immune Responses in Human Dendritic Cells Mediated by Retinoic Acid Receptor Alpha Ligation - Bene, Krisztian; Varga, Zsofia; Petrov, Viktor O.; Boyko, Nadiya; Rajnavolgyi, Eva (Frontiers in Immunology, 2017)
Dendritic cells (DCs) are considered as the main coordinators of both mucosal and systemic immune responses thus playing a determining role in shaping the outcome of effector cell responses. However, it is still uncovered how primary human monocyte-derived DC populations (moDC) drive the polarization of helper T (Th) cells in the presence of commensal bacteria harboring unique immunomodulatory properties. Furthermore, the individual members of the gut microbiota have the potential to modulate the outcome of immune responses and shape the immunogenicity of differentiating moDCs via the activation of retinoic-acid receptor alpha (RARα). Here we report that moDCs are able to mediate robust Th1 and Th17 responses upon stimulation by Escherichia coli Schaedler or Morganella morganii, while the probiotic Bacillus subtilis strain limits this effect. Moreover, physiological concentrations of all-trans retinoic-acid (ATRA) are able to re-program the differentiation of moDCs resulting in altered gene expression profiles of the master transcription factors RARα and interferon-regulatory factor (IRF) 4, and concomitantly regulate the cell surface expression levels of CD1 proteins and also the mucosa-associated CD103 integrin to different directions. It was also demonstrated that the ATRA-conditioned moDCs exhibited enhanced pro-inflammatory cytokine secretion, while reduced their co-stimulatory and antigen presenting capacity thus reducing Th1 and presenting undetectable Th17 type responses against the tested microbiota strains. Importantly, these regulatory circuits could be prevented by the selective inhibition of RARα functionality. These results altogether demonstrate that selected commensal bacterial strains are able to drive strong effector immune responses by moDCs, while in the presence of ATRA they support the development of both tolerogenic and inflammatory moDC in a RARα dependent manner.